Association between size-resolved PM10-bound heavy metal and metalloid exposure and oxidative stress among waste recycling workers - Xing Li; Ying Guo (Scientific Reports)
Abstract Following the sharp increase in global waste generation, heavy metals and metalloids (HMMs) have become a serious threat to workers in the waste recycling industry. However, our understanding of internal exposure levels of HMMs and the relationship between size-resolved particulate matter (PM)-bound HMMs external exposure with internal exposure and oxidative stress among waste recycling workers are limited. Therefore, we collected first morning void urine samples from 20 participants and size-resolved indoor PM10 samples at least 45 consecutive days. We then detected 21 urinary HMMs, PM10-bound HMMs and oxidative stress biomarkers (OSBs) of DNA (8-hydroxy-2′-deoxyguanosine [8-OHdG]) and lipids [malondialdehyde (MDA)]. The intraclass correlation coefficients for most HMMs and OSBs ranged from fair to excellent. Linear mixed model analysis showed that urinary HMMs were predominantly affected by warehouse PM1.1–2.1 and PM3.3–4.7 HMM inhalation (p < 0.05). Participant 8-OHdG levels were correlated with PM0.43–10 HMM inhalation, particularly in the ranges of PM0.43–0.65, PM4.7–5.8, and PM9.0–10, with every unit increase in the ln-transformed average daily intake (ADI) generating a 4.30–28.0% increase in urinary 8-OHdG (p < 0.05). Furthermore, MDA levels were generally correlated with PM0.43–2.1 HMM inhalation (p < 0.05), especially in the PM0.43–0.65 range, with each unit increase in the ln-transformed ADI generating a 8.5–24.1% increase in urinary MDA. This study reveals the fair to excellent long-term reproducibility of urinary HMM and OSBs and the association between high-level PM-bound HMM exposure and early health impairment for an actual working environment.